A compact multi-parameter detection system based on hydrodynamic sequential injection for sensitive determination of phosphate, nitrite, and nitrate in water samples - Wanpen Khongpet (2020)
© The Royal Society of Chemistry 2020. A miniaturized microfluidic hydrodynamic sequential injection system for multi-parameter analysis with a sensitive colorimetric detection was developed to improve the analytical performance for the measurement of phosphate, nitrite, and nitrate based on molybdenum blue and Griess methods. A homemade colorimetric detection with a light emitting diode as a light source and phototransistor light sensor was integrated into the microfluidic platform to achieve a low cost compact system with low reagent consumption and high sensitivity. Under the optimized working conditions, a linear calibration graph of phosphate (two working range), nitrite and nitrate (as nitrogen, N) in the range of 0.01-0.1 and 0.3-1.0 mg of PO43- P L-1, 0.005-0.05 mg of NO2- N L-1 and 0.01-0.12 mg of NO3- N L-1, respectively were achieved with a sample-throughput of 10 h-1. The limit of detections were 0.005 mg of PO43- P L-1, 0.0026 mg of NO2- N L-1 and 0.005 mg of NO3- N L-1. The percentage of recovery for phosphate, nitrite, and nitrate were 90.3-115.0, 90.0-117.0 and 91.3-117.0, respectively, with relative standard deviations in the range of 1.07-4.90%. Capabilities of the developed device for consecutive analysis of multiple analytes were demonstrated to be an excellent choice for water quality monitoring.